1-Octanol emitted by Oecophylla smaragdina weaver ants repels and deters oviposition in Queensland fruit fly - Vivek Kempraj; Soo Jean Park; Donald N. S. Cameron; Phillip W. Taylor (Scientific Reports, 2022)
Abstract Humans have used weaver ants, Oecophylla smaragdina, as biological control agents to control insect pests in orchards for many centuries. Over recent decades, the effectiveness of weaver ants as biological control agents has been attributed in part to deterrent and oviposition inhibiting effects of kairomones produced by the ants, but the chemical identity of these kairomones has remained unknown. We have identified the kairomone responsible for deterrence and oviposition inhibition by O. smaragdina, providing a significant advance in understanding the chemical basis of their predator/prey interactions. Olfactometer assays with extracts from weaver ants demonstrated headspace volatiles to be highly repellent to Queensland fruit fly, Bactrocera tryoni. Using electrophysiology and bioassays, we demonstrate that this repellence is induced by a single compound, 1-octanol. Of 16 compounds identified in O. smaragdina headspace, only 1-octanol evoked an electrophysiological response from B. tryoni antennae. Flies had greatly reduced oviposition and spent significantly less time in an olfactometer arm in the presence of 1-octanol or a synthetic blend of headspace volatiles containing 1-octanol than in the presence of a synthetic blend of headspace volatiles without 1-octanol, or clean air. Taken together, our results demonstrate that 1-octanol is the functional kairomone component of O. smaragdina headspace that explains repellence and oviposition deterrence, and is hence an important contributor to the effectiveness of these ants as biological control agents.